Mendelian randomization analyses support causal relationship between brain imaging-derived phenotypes and risk of low back pain - Xiao-Yan Xie; Jian-Wei Lin; Jia-Yu Fang; Zhuo-Chen Chen; Peng-Cheng Li; Xiao-Yan Huang; Ming-Yan Guo; Li-Ling Lin; Ming-Hui Cao (Brain Research Bulletin)
Low back pain (LBP) has long been the leading cause of worldwide productivity loss and the top cause of years lived with disability. Observational studies have reported associations between brain imaging-derived phenotypes (IDPs) and LBP; however, it is uncertain whether these relationships are causal. Bidirectional two-sample Mendelian randomization (MR) analyses were applied to explore the causal relationship between IDPs and LBP. Summary data of 587 brain IDPs (N = 33,224 individuals) from the UK Biobank and LBP (13,178 cases and 164,682 controls) from the FinnGen database were obtained respectively. Inverse variance weighted (IVW) was used as the primary MR analysis method. The MR Egger, Weighted median, Simple mode, Weighted mode, MR-RAPS, BWMR were supplemented. Sensitivity analyses were applied to demonstrate the reliability of the results. 45 IDPs were identified for which there was evidence of a causal impact on the risk of LBP in total. Forward MR identified 12 IDPs associated with a higher risk of LBP (odds ratio, OR range from 1.06 to 1.93, P ＜0.05) and 19 IDPs associated with a lower risk of LBP (OR range from 0.61 to 0.92, P ＜0.05). Reverse MR showed that genetically predicted LBP was positively correlated with 6 IDPs (β range from 0.10 to 0.17, P ＜0.05) and negatively correlated with 8 IDPs (β range from −0.15 to −0.10, P ＜0.05). There is a relationship between IDPs and LBP risk. Our findings provide potential strategies for predicting LBP risk at the brain-imaging level.